Fundamentals of Entrepreneurship (ENT300) : Nak cendol cafe / Fiefi Fariesha Mohamad … [et al.] - Mohamad, Fiefi Fariesha; Loren, Norhafizah; Kolek, Norshahaziera; Mohd Annuar, Nur Effa Idayu; Julaihie, Nur Fatin Syamimi; Rozui @ Rozey, Nurul Qatrunada (2018)
“Nak cendol” cafe was established and started the operation on year 2017 with a new innovation of their main product which is "cendol” itself. The owner did some innovation and create new taste in every product that they serve. Since there is many cafe or restaurant serve the same menu, however, the “nak cencol” cafe is different than other cafe that have been established. They provides a quality product in serving their customer by having certificates for their cafe.